Book of Ordinances of the Town of Freehold, New Jersey 54 (1894) - (:unkn) unknown (My University, 1894)
That if any person or persons shall fire, discharge, or let off any gun, pistol, squib, or other fire-work within this town within one hundred yards of any dwelling house, stable, or any other building, every such person or persons so offending and being thereof duly convicted, shall forfeit and pay for every such offense the sum of Five Dollars
Keywords: DISCHARGE